La secretaria ejecutiva gerencial en la organización de eventos y logística dentro del patronato municipal de amparo social del cantón Salcedo - Guanoluisa Chuqui, Sandy Maribel (2015)
The purpose of this research paper is the elaboration of a guide for the organization of events and logistics. This work was prepared for the management of the Executive Secretary of the Patronato Municipal de Amparo Social del Cantón Salcedo with the intention to resolve the institution's problem in that area. Where the problem was made by deficiencies on event holdings. At first step, this essay is based on the activities those are considered necessary for holding an event, where are researched important topics such as general marketing characteristics, corporative image, public relations and the organization of events and logistics….